Causative organisms of urinary tract infections and their drug sensitivity: an analysis from various aspects - Li, Xinwei; Zhang, Yuanpeng; Xiao, Wen; Zhang, Xiaoping; Liu, Lei (Frontiers in Public Health, 2025)
ObjectiveUrinary tract infection is a prevalent and complex clinical condition. To treat urinary tract infections more effectively, we sought to describe the distribution and antibiotic susceptibility of causative organisms in patients.Materials and methodsWe retrospectively analyzed 3,685 patients with urinary tract infections between 2022 and 2023, treated at the Department of Urology of Wuhan Union Hospital. Clinical data, urine culture results, and drug sensitivity test data were collected for further analysis.ResultsOf all 3,685 patients with positive urine cultures, 3,899 strains of causative organisms were isolated. Gram-negative bacteria (2,242/3899, 57.50%) were the most common causative organisms, among which Escherichia coli (1,250/3899, 32.06%) was the most common species. Drug sensitivity tests showed that most pathogens exhibited high sensitivity to restricted antibiotics (e.g., carbapenems) and cephalosporins (nearly 100 and 90%, respectively), but high resistance rates to quinolones and macrolides (over 50%). Comparing the distribution of causative organisms and drug sensitivity between 2022 and 2023, we found that the proportion of E. coli and Proteus mirabilis have increased significantly (p = 0.0066 and p = 0.0003, respectively), while the proportion of Enterococcus faecium have decreased significantly (p = 0.0419). Compared to non-stone infections, stone-associated infections showed a significantly higher proportion of P. mirabilis (p < 0.0001), consistent with its role in magnesium ammonium phosphate stones formation. Significant differences in pathogen distribution were also observed between outpatient and ward settings (E. coli, Enterococcus faecalis, Klebsiella pneumoniae, Staphylococcus epidermidis, Enterobacter aerogenes, E. faecium, Pseudomonas aeruginosa, and Acinetobacter baumannii).ConclusionBased on the above results, cephalosporins are recommended to be applied in the initial empirical treatment, with timely adjustment according to the results of antimicrobial susceptibility testing.